2023
DOI: 10.1136/gutjnl-2022-328845
|View full text |Cite
|
Sign up to set email alerts
|

Targeting m6A reader YTHDF1 augments antitumour immunity and boosts anti-PD-1 efficacy in colorectal cancer

Abstract: ObjectiveThe role of N6-methyladenosine (m6A) in tumour immune microenvironment (TIME) remains understudied. Here, we elucidate function and mechanism of YTH N6-methyladenosine RNA binding protein 1 (YTHDF1) in colorectal cancer (CRC) TIME.DesignClinical significance of YTHDF1 was assessed in tissue microarrays (N=408) and TCGA (N=526) cohorts.YTHDF1function was determined in syngeneic tumours, intestine-specificYthdf1knockin mice, and humanised mice. Single-cell RNA-seq (scRNA-seq) was employed to profile TIM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
45
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 109 publications
(46 citation statements)
references
References 36 publications
1
45
0
Order By: Relevance
“…CT26 tumor model was characterized as "cold tumors" owing to their immunosuppressive microenvironment, resulting in a diminished sensitivity to tumor immunotherapy interventions. 28 The inherent challenge in tumor immunotherapy lies in the low reactivity of "cold tumors", impeding effective responses to immunotherapeutic interventions. To explore the in vivo therapeutic efficacy of Flow cytometric analysis of tumor-infiltrating immune cells provided insights into the impact of X22 on the tumor immune microenvironment, particularly focusing on key immunosuppressive Treg and MDSC cells, and CD8 + T cells, which are essential for tumor-killing.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…CT26 tumor model was characterized as "cold tumors" owing to their immunosuppressive microenvironment, resulting in a diminished sensitivity to tumor immunotherapy interventions. 28 The inherent challenge in tumor immunotherapy lies in the low reactivity of "cold tumors", impeding effective responses to immunotherapeutic interventions. To explore the in vivo therapeutic efficacy of Flow cytometric analysis of tumor-infiltrating immune cells provided insights into the impact of X22 on the tumor immune microenvironment, particularly focusing on key immunosuppressive Treg and MDSC cells, and CD8 + T cells, which are essential for tumor-killing.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…In a recent report, intestine-specific YTHDF1 knock-in promotes MDSC migration, antagonizing functional CD8 + T cells in the TIME enhancing CRC growth. In this case, YTHDF1 activates the CXCL1-CXCR2 axis to promote m 6 A-p65 translation [143].…”
Section: Cancer Immunoevasionmentioning
confidence: 99%
“…Recent studies have shown that epigenetic regulation, speci cally N 6 -methyl adenosine (m 6 A) modi cation, holds substantial importance in the immune microenvironment of tumors. The presence of m 6 A in uences the activation, invasion, proliferation, and effector function of immune cells that in ltrate the tumor [5,6] . Furthermore, research indicates that targeting m 6 A can impact the response rate of immunotherapy, highlighting its potential as a target for sensitizing immunotherapy [7,8] .…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, research indicates that targeting m 6 A can impact the response rate of immunotherapy, highlighting its potential as a target for sensitizing immunotherapy [7,8] . Three protein factors, namely methyltransferase as the writers (METTL3, METTL14, etc), binding protein as the readers (YTHDF1, YTHDF2, YTHDC1, etc), and demethylase as the erasers (FTO, ALKBH5, etc), participate in and regulate the modi cation of m 6 A [5,9,10] .The core methyltransferase complex METTL3-METTL14-WTAP m 6 A catalyzes the procedure, while two key erasers, FTO and ALKBH5, remove the modi cation [11][12][13] .…”
Section: Introductionmentioning
confidence: 99%